ANALYSIS OF PROFITABILITY PERFORMANCE: THE COMPARISON OF BPR KOTA BARU AND BPR IN SOUTH KALIMANTAN PROVINCE DURING COVID-19 PANDEMIC PERIOD - Supeno, Wangsit (Universitas Sam Ratulangi, 2021)
The impact of the Covid-19 pandemic is strongly felt for the Rural Banks (or BPR) industry operating in South Kalimantan province. This study is a case study of BPR Kota Baru operating in South Kalimantan Province. Based on the financial report published by Financial Services Authority (or OJK), the BPR Kota Baru is one of the banks that has the best Return On Asset (ROA) performance, because the ROA ratio continues to grow during the Covid-19 pandemic. The purpose of this study is to find out the extent of the performance of Return On Asset or ROA of BPR Kota Baru compared to the ROA Performance of some BPR in South Kalimantan Province before and during the Covid-19 pandemic has a positive ROA. Analysis of research data is sourced from the financial statements of conventional BPR publications accessed on the website of OJK. This study conducts comparative research methods and finds that during the Covid-19 pandemic the ROA of BPR Kota Baru for September 2020 is 6.74% while the average ROA ratio of other BPR is 4.80%. On asset management and operational cost efficiency to operating income (BOPO), the management of BPR Kota Baru manage to improve profitability capability in the midst of the Covid-19 pandemic in the position of financial statements published in September 2020.